The impact of family ownership on firms' performance: A study of firms in the South African Clothing and Textiles manufacturing industry 2009-2011 - Ntsalaze, Lungile (Research of GSB, 2018)
Family businesses have been prevalent throughout history for the way in which they are able to combine family interests with those of the business. However, it is only recently-that the world has begun to recognize its signiﬁcance and uniqueness. Stimulated by this recognition, there is a steadily growing body of academic knowledge that has started to consolidate more insight into the characteristics of the family birthed and operated enterprise as a viable business model. The history suggests that family businesses have played an integral role in nation building and for an emerging market environment like South Africa, could hold one of the keys to accelerate much needed broad-based economic advancement and participation. This study was shaped from a keen interest in investigating the tacit value that family owned business models can yield by conducting a comparative panel study of performance between family and non-family firms in the Clothing and Textiles manufacturing industry in the South African IDC portfolio (2009-2011). Key ﬁnancial metrics, namely to return on assets, return on equity, income security cover, outside funds to cash flow and shareholders' funds to total assets were referenced. Regression analysis was used to estimate the relationship between performance and ﬁrms. Both qualitative and quantitative approaches were employed in the study to arrive at the results. Although studies have been conducted to show that family-controlled firms seem to perform worse than non-family ﬁrms, the results from this study show that family business performed better on return on assets when applying the data set in a regression analysis technique. The results also show that, founder and ﬁrst generation owners have a signiﬁcant impact on family business performance. Given the importance of family businesses, in terms of employment creation, informal training (skills development) and the economy at large, it is therefore critical that all efforts be made to assist the owners of family businesses to deal with the complex challenges they face to ensure their survival and growth.